Design and Simulation Of Robotic Spot Welding System for Automotive Manufacturing Application - M. F. F., Ab Rashid; Wan Mansor, Wan Muhamad; M., Ishak; Mohd Zaidi, Sidek (2005)
Spot welding process for automotive manufacturing application is moving towards automation and robotic level. The transition process from manual to automation system need a proper planning and know how. Simulation is the best solution for predicting, comparing or optimizing the performance of a process without the risk of disrupting existing operations or cost of implementing a new actual process. This paper presents the application of simulation and statistical analysis for replacing a manual welding system of a body shop assembly with a robotic spot welding system (RSWS). Initially, the RSWS developed uses a minimum number of robots for producing the same number of output as before. Robot selection analysis was performed using Multi-Attribute Decision Making method. The CAD model was built using Solidworks software and simulation was performed using Robotworks software. The data that was acquired from robot workcell simulation were transferred to Witness software for purpose of shop floor simulation. The results from Witness simulation show that the new welding layout is capable of achieving the manufacturer’s target. The analysis shows results of lower operational cost and the break event point will be achieved by the third year of operation. The implementation of RSWS for automotive application is reasonable because of efficiency, accuracy and cost effective.